The Idea of Pluralism in Indonesian Society: A Case Study of Cirebon City as a Cultural Melting Pot - Soekarba, Siti Rohmah (UI Scholars Hub, 2018)
Indonesia is well-known as a country with diverse ethnicities, religions, and races. Although predominantly Muslim country, the largest population of Muslims of any country in the world today, the reminder of the population are Christians, Hindu, animist, or followers of varying Confucius and Buddhist beliefs. Indonesia today is not only a country with diverse religions, ethnicities, and races, but also a country with several challenges related to issues of religious pluralism.It takes the awareness and the political will to deconstruct what lies behind the various problems of the Indonesian nation by looking back to the Indonesian national identity as stated in the Pancasila principles and the 1945 Constitution. Indonesia's national motto,